Feasibility and effectiveness of seal deterrent in coastal trap-net fishing – development of a novel mobile deterrent - Lehtonen, Esa; Lehmonen, Roope; Kostensalo, Joel; Kurkilahti, Mika; Suuronen, Petri (Elsevier BV, 2022)
With the rapid growth of grey seal (Halichoerus grypus) population in the Baltic Sea, seal-induced catch losses have increased dramatically in coastal fisheries. There have been various attempts to mitigate these damages, such as modification of fishing gear, but solutions have proven inadequate. Promising research results have recently been obtained by using acoustic deterrent devices (ADDs) to keep seals away from the immediate vicinity of the gear. We tested the feasibility and effectiveness of a raft-mounted and a novel mobile ADD in Baltic salmon (Salmo salar) trap-net fisheries along the Finnish coast in collaboration with 13 commercial fishers. Fishers operated trap-nets (pontoon traps) that were equipped with and without an ADD. Our results indicate that a fisher with a trap-net equipped with an ADD can expect to catch on average 3.4 salmon per day whereas in trap-net without an ADD a fisher can expect on average 2.1 salmon per day. The deployment of ADDs over the two years testing period indicated an average increase of 64% in salmon catches. Our study suggests that in salmon trap-net fisheries an ADD is a useful and economically viable (given that the investment is subsided) mitigation tool for reducing seal-induced catch losses. Furthermore, the mobile ADD developed in this study provides unique practical opportunities and notable potential for a wider use of an ADD.
Keywords: grey seal; acoustic deterrent device; salmon; Bayesian analysis; Seal-fishery conflict; Halichoerus grypus; Baltic salmon; ADD